2017
DOI: 10.1089/aid.2016.0205
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Transmission Clusters with Cluster Picker and HIV-TRACE

Abstract: We compared the behavior of two approaches (Cluster Picker and HIV-TRACE) at varying genetic distances to identify transmission clusters. We used three HIV gp41 sequence datasets originating from the Rakai Community Cohort Study: (1) next-generation sequence (NGS) data from nine linked couples; (2) NGS data from longitudinal sampling of 14 individuals; and (3) Sanger consensus sequences from a cross-sectional dataset (n = 1,022) containing 91 epidemiologically linked heterosexual couples. We calculated the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 33 publications
3
58
0
Order By: Relevance
“…One should consider exploring the choice of more stringent cut-offs between 0.01 and 0.02 for example to identify potential transmission partnerships and networks particularly in settings with high-risk HIV transmission to avoid additional complexity of finding spurious associations. A large study (~20,000 sequences) that evaluated the number, size, and composition of clusters detected by Cluster Picker and HIV-TRACE at six genetic distance thresholds (1%–5.3%) on three gp41 datasets showed that the optimal gp41 genetic distance threshold to distinguish linked and unlinked couples and individuals was 5.3% and 4.0%, respectively [53]. Another potential limitation was that we were unable to estimate the proportion of HIV infections attributable to community contacts or outside community, in the absence of historical contacts.…”
Section: Discussionmentioning
confidence: 99%
“…One should consider exploring the choice of more stringent cut-offs between 0.01 and 0.02 for example to identify potential transmission partnerships and networks particularly in settings with high-risk HIV transmission to avoid additional complexity of finding spurious associations. A large study (~20,000 sequences) that evaluated the number, size, and composition of clusters detected by Cluster Picker and HIV-TRACE at six genetic distance thresholds (1%–5.3%) on three gp41 datasets showed that the optimal gp41 genetic distance threshold to distinguish linked and unlinked couples and individuals was 5.3% and 4.0%, respectively [53]. Another potential limitation was that we were unable to estimate the proportion of HIV infections attributable to community contacts or outside community, in the absence of historical contacts.…”
Section: Discussionmentioning
confidence: 99%
“…We compare two HIV network inference tools: HIV-TRACE (Kosakovsky and TreeCluster (Moshiri, 2018). HIV-TRACE is a widely-used method (Rose et al, 2017;Wertheim et al, 2017;Pérez-Losada et al, 2017) that clusters individuals such that, for all pairs of individuals u and v, if the Tamura and Nei (1993) (TN93) distance is below the threshold (default 1.5%), u and v are connected by an edge; each connected component forms a cluster. When we ran HIV-TRACE, we skipped its alignment step because we did not simulate indels.…”
Section: Transmission Network Reconstruction Methodsmentioning
confidence: 99%
“…According to the Cluster Picker manual and the suggestions of previous studies, the parameter support threshold was set to 0 and the genetic distance threshold was set to 4% to identify a close transmission relationship between Yunnan-mIDUs and Dehong IDUs [2224,38]. …”
Section: Methodsmentioning
confidence: 99%